32.0k views
4 votes
How would the sum of cubes formula be use to factor x^3y^3+343?Explain the process

User Pva
by
5.1k points

2 Answers

5 votes

Answer:

Explanation:

To factor, first identify the quantities that are being cubed. The first term is the cube of xy, and the constant is the cube of 7. Next, use the formula to write the factors. The first factor is the sum of xy and 7. The second factor has three terms: the square of xy, the negative of 7xy, and the square of 7.

User Joel Green
by
5.3k points
3 votes
The formula of perfect cubes is given by:

a ^ 3 + b ^ 3 = (a + b) (a ^ 2 - ab + b ^ 2)
We have the following expression:

x ^ 3y ^ 3 + 343
For this case:

a ^ 3 = x ^ 3y ^ 3 b ^ 3 = 343
Therefore, the values a and b are:

a = (x ^ 3y ^ 3) ^ {(1/3)} = xy b = (343) ^ {(1/3)} = 7
Substituting values we have:

(xy + 7) (x ^ 2y ^ 2 - 7xy + 49)
Answer:
The equivalent expression is:

(xy + 7) (x ^ 2y ^ 2 - 7xy + 49)
User Deproblemify
by
4.8k points